Trends in Complications Following Pediatric Anterior Cruciate Ligament Reconstruction as Reported to the American Board of Orthopaedic Surgery Part II Oral Examination Database - Dane R.G. Lind, BA; Meagan J. Sabatino, MSL; Virginia C. Clark, BS; Robert L. Van Pelt, MPH; Curtis D. Vandenberg, MD; Jennifer J. Beck, MD; Andrew T. Pennock, MD; Aristides I. Cruz, Jr., MD, MBA; Theodore J. Ganley, MD; Kevin G. Shea, MD; Philip L. Wilson, MD; Henry B. Ellis, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: Pediatric anterior cruciate ligament reconstructions (ACLR) have increased dramatically in recent years. However, a comprehensive list of short-term complications related to this procedure has yet to be reported. This study aimed to report complication rates in pediatric ACLR using submissions to the American Board of Orthopaedic Surgery (ABOS) Part II Oral Examination. A secondary goal was to assess the relationship of complications with patient sex, geographic region of surgery, surgical volume, and surgeon fellowship training. Methods: A query was submitted to the ABOS Part II Oral Examination Case List Database for all ACLR performed in patients younger than 19 years between 2000 and 2021. Surgeon fellowship training, geographic region of surgery, and patient demographics were included, along with medical, surgical, and anesthetic complications, reoperation, and readmission. Statistic comparisons used chi-square tests for categorical variables with significance set at P < 0.05. Results: Surgical complications were the most common type of complication, present in 10.1% of pediatric ACLR. Stiffness (3.6%) and infection (1.5%) were the most prevalent surgical complications. Females had higher rates of overall complications than males (11.9% vs. 10.4%, P = 0.010). Females also had higher rates of surgical complications (10.7%–9.5%, P = 0.019) -- specifically stiffness (5.0%–2.2%, P < 0.001). However, males had higher rates of infection (1.8% vs. 1.3%, P = 0.047). Geographic analyses showed higher infection rates in Hawaii and Alaska and lower surgical complication rates in the Northwest region. Procedures completed by surgeons with a fellowship training other than Sports Medicine and/or Pediatric Orthopaedics had lower rates of overall complications (8.9%, P < 0.001) and surgical complications (8.3%, P < 0.001). Conclusion: This study establishes that female pediatric and adolescent patients are at an increased risk for complications following ACLR. Arthrofibrosis was more than twice as common in females than in males. Geographic region and fellowship training may be associated with complications in this population. Study design: Cross-Sectional Study Key Concepts: (1) Complications following ACL reconstruction may be associated with geographic region and fellowship training. (2) Females present with more short-term complications following ACL reconstruction. (3) There was a higher reported infection rate overall for surgeons in their board collection period than infection rates in the literature, with males having an overall higher infection rate than females. (4) Arthrofibrosis is more than twice as common in females than males following ACL reconstruction. Level of Evidence: III